Corrosion and wear resistance properties of multilayered diamond‐like carbon nanocomposite coating. (8th January 2018) - Viswanathan, S.; Mohan, L.; Bera, Parthasarathi; Shanthiswaroop, S.; Muniprakash, M.; Barshilia, Harish C.; Anandan, C.
Abstract : Multilayered diamond‐like carbon (DLC) nanocomposite coating has been deposited on silicon and stainless steel substrates by combination of cathodic arc evaporation and magnetron sputtering. In order to make DLC coating adhered to metal substrate, a chromium interlayer has been deposited with constant bias voltage of −150 V applied to the substrate. Dense multilayered coating consists of metallic or nonmetallic and tetrahedral carbon (ta‐C) layers with total thickness of 1.44 μm. The coating has been studied for composition, morphology, surface nature, nanohardness, corrosion resistance, and tribological properties. The composition of the coating has been estimated by energy‐dispersive spectroscopy. Field‐emission scanning electron microscopy and atomic force microscopy have been used to study the surface morphology and topography. I D / I G ratio of ta‐C:N layer obtained from Raman spectroscopy is 1.2, indicating the disorder in the layer. X‐ray photoelectron spectroscopy studies of individual ta‐C:N, CrN, and Cr‐doped DLC layers confirm the presence of sp 2 C, sp 3 C, CrN, Cr2 N, and carbidic carbon, and sp 2 C, sp 3 C, and Cr carbide. Nanohardness studies show the maximum penetration depth of 70 to 85 nm. Average nanohardness of the multilayered DLC coating is found to be 35 ± 2.8 GPa, and Young's modulus is 270 GPa. The coating demonstrates superior corrosion resistance with better passivation behavior in 3.5% NaCl solution, and corrosion potential is observed to move towards nobler (more positive) values. A low coefficient of friction (0.11) at different loads is observed from reciprocating wear studies. Wear volume is lower at all loads on the multilayered DLC nanocomposite coating compared to the substrate.